Plasmepsin II-III copy number accounts for bimodal piperaquine resistance among Cambodian Plasmodium falciparum - Bopp, S; Magistrado, P; Wong, W; Schaffner, S; Mukherjee, A; Lim, P; Dhorda, M; Amaratunga, C; Woodrow, C; Ashley, E; White, N; Dondorp, A; et al. (Nature Publishing Group, 2018)
Multidrug resistant Plasmodium falciparum in Southeast Asia endangers regional malaria elimination and threatens to spread to other malaria endemic areas. Understanding mechanisms of piperaquine (PPQ) resistance is crucial for tracking its emergence and spread, and to develop effective strategies for overcoming it. Here we analyze a mechanism of PPQ resistance in Cambodian parasites. Isolates exhibit a bimodal dose-response curve when exposed to PPQ, with the area under the curve quantifying their survival in vitro. Increased copy number for plasmepsin II and plasmepsin III appears to explain enhanced survival when exposed to PPQ in most, but not all cases. A panel of isogenic subclones reinforces the importance of plasmepsin II-III copy number to enhanced PPQ survival. We conjecture that factors producing increased parasite survival under PPQ exposure in vitro may drive clinical PPQ failures in the field.